EVALUATION OF THE CODAL PROVISION FOR ASYMMETRIC BUILDING - Priyanshu Chandrakar; Kirti Sahu (International Journal of Innovations in Engineering Research and Technology, 2021)
The research on asymmetric buildings has been extensive primarily focusing on the stability of a structure when subjected to earthquake. Based on them numerous guidelines are laid out for to make sure safety. I have during this paper tried to guage the effectiveness of the rules provided within the IS: 1893 (2000). Asymmetric buildings are more common now than they have ever been and their popularity has been growing primarily due to the functionality they provide. Due to the frequent earthquakes that India suffers, being at the junction of two tectonic plates it has become increasingly important to review Indian buildings for seismic safety. The buildings are analyzed supported the effect of torsion which is that the main explanation for damage for Asymmetric Buildings.